PELATIHAN PENGELOLAAN EVENT KESENIAN TARI DI DESA TULUS BESAR - Isnaini Nur Safitri; Pritantina Yuni Lestari; Candrika Citra Sari; Tri Astuti Handayani; Hilda Cahyani; Titien Indrianti (P3M Politeknik Negeri Malang, 2026)
This community service is aimed at accommodating the needs of the Tulus Besar Village community, Tumpang District, in increasing their knowledge regarding dance event management in Tulus Besar Village by involving dance artists in Tulus Besar Village through the Dance Event Management Training. With this training, it is hoped that it can improve the quality of dance performances and the skills of dance artists in Tulus Besar Village in planning and managing performances sustainably. Participants in this training are dance artists and Tulus Besar village officials. Through this activity, it is hoped that there will be an increase both in knowledge also the economic value of tourism and arts potential. In addition, it is also hoped that the quality of human resources of dance artists and village officials can improve, especially in terms of the ability to manage sustainable dance performances. This activity will be carried out in seven stages, namely planning (to find out the number of participants and the materials needed), preparation and coordination with the proposing team and the village, socialization, event management training, periodic event mentoring, monitoring and evaluation (to get feedback and information from training participants), and the last is publication.